When Occupational Cancer Recognition Falters - Assennato, Giorgio; De Giampaulis, Chiara (La Medicina del Lavoro, 2025)
There are differences between epidemiology and legal medicine in addressing the problem of under-reporting occupational cancers. Epidemiology focuses on systematically gathering data and identifying patterns of under-reporting, which is not deemed to pose ethical dilemmas, as its goal is to improve public health outcomes. Conversely, legal medicine investigates individual cases and ensures compliance with legal standards, presenting more complex ethical challenges. Considering workers' frustrations when dealing with unrecognized occupational diseases is essential. These workers experience significant physical and emotional distress and should not have to face a complicated compensation claims process. There is a need for ethical approaches that support workers in navigating their rightful claims for compensation, not challenging their mental and emotional well-being.